2016
DOI: 10.21037/tgh.2016.03.16
|View full text |Cite
|
Sign up to set email alerts
|

A review on robotic surgery in rectal cancer

Abstract: Robotic surgery has the upper hand when compared to the laparoscopic approach in terms of superior visualisation, flexibility in movement, steadiness and accessibility to confined anatomical spaces.Nevertheless, limitations still exist with regards to cost, reduced tactile sensation, time-consuming setup and a significant learning curve to achieve. Although studies have shown better or at least comparable outcomes between the robotic and laparoscopic approach, the limitations mentioned result in poor penetranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In the past decade, robotic surgery has been utilized successfully in various surgeries due to its advantages of three‐dimensional vision, increased dexterity of movement, and decreased fatigue . A meta‐analysis of eight studies, mostly non‐RCTs, evaluated the safety and efficacy of robotic total mesorectal excision in rectal cancer patients and concluded that robotic surgery was associated with a lower conversion rate (OR 0.23), fewer positive circumferential resection margins (OR 0.44), and a lower incidence of erectile dysfunction (OR 0.09) than laparoscopic surgery .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, robotic surgery has been utilized successfully in various surgeries due to its advantages of three‐dimensional vision, increased dexterity of movement, and decreased fatigue . A meta‐analysis of eight studies, mostly non‐RCTs, evaluated the safety and efficacy of robotic total mesorectal excision in rectal cancer patients and concluded that robotic surgery was associated with a lower conversion rate (OR 0.23), fewer positive circumferential resection margins (OR 0.44), and a lower incidence of erectile dysfunction (OR 0.09) than laparoscopic surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic TME (LTME) has apparent advantages and considered a preferred mode of surgery due to less tissue trauma[ 5 - 11 ]. Due to precision in dissection, stable base unit and better visualization in difficult areas like lower pelvis, the robotic TME (RTME) is also considered a possible alternative to LTME[ 12 , 13 ]. RTME may potentially offer same advantages which LTME offers as reported in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting results have been reported regarding the impact of the previous proficiency on laparoscopy on the duration of the period [45,46] . Most of the publications evaluated the expertise with variables as "operative time", "bleeding" or "conversion" which may not be the most critical outcomes [47] . There is a wide agreement on the fact that operative times are longer during a learning curve, but a recent study on robotic rectal resection showed no relationship between extended operative time and morbidity [48] .…”
Section: Learning Curve Of Robotic Tmementioning
confidence: 99%
“…Current robotic platforms display a 3D image, enhancing the visualization of the anatomical structures by improving the surgeon's depth perception and image quality. Compared to conventional laparoscopy, robotic surgery also allows to control a stable camera [47] . The system has recently incorporated the EndoWrist® technology, which improves dexterity and eliminates physiological tremor reducing the challenge of laparoscopic intra-corporeal suturing [51] .…”
Section: Technical Advantagesmentioning
confidence: 99%
See 1 more Smart Citation